Third generation R&D : - Roussel, Philip A. (Harvard Business School Press, 1991)
Written by three senior consultants from Arthur D. Little, this book provides managers with a new approach that will make R&D a truly competitive weapon. Relates how R&D management has evolved from the naive "strategy of hope" approach of the 1950s and 1960s, when companies spent lavishly in the vague expectation that something good would result, to the more systematic approach of the past two decades. The third generation of R&D is a pragmatic method for linking R&D to long-term business planning. It shows managers how to: integrate technology and research capabilities with overall management and strategy; break down organizational barriers that isolate R&D from the rest of the company; foster a spirit of partnership and trust between R&D and other units; and create managed portfolios of R&D projects that match corporate goals.